Solar Energy Challenges for Rural Electrification: Case Study of Lower-Shabelle Region of Somalia - Mohamed Adam Mohamed; Osman, Shahrul Azmir; Nasir, Nurul Fitriah (International Journal of Integrated Engineering, 2024)
Renewable energy is a promising energy source for sustainability to meet the demands of clean energy in the future and the alternative way of fusil fuels. Somalia has great potential for alternative energy sources, particularly solar and wind power. Apart from that, there are challenges related to the implementation of this alternative energy source especially solar energy for rural electrification in Lower-Shabelle region in Somalia which can be categorized as social awareness, financial difficulties, and technical obstacles. So, the aim of this research is to identify and evaluate the challenges of solar energy for rural electrification in Lower-Shabelle region in Somalia, the current energy sources that have been utilized and the possible future strategies that should be in Somalia. This research project is conducted through a survey using an online questionnaire that has been distributed in Afgooye district in Lower-Shabelle region in Somalia. The statistical model of IBM SPSS version 25 was used to study the descriptive analysis of the collected data, reliability analysis and distribution test analysis. Based on the statistical analysis, the results indicated the significance impact of scattered settlement pattern of rural people in this area, traditional way of living of rural people and dependence on conventional energy source, the high cost of import for the off-grid products, low-rate of return from solar projects in rural areas, shortage or lack of technical knowledge of solar technologies in this region and other technical challenges related to solar technologies efficiency like battery overcharge and poor layout of solar panels where most of the respondents agreed about these challenges.